Natural disasters and challenges toward achieving food security response in Iran - Soheyla Ainehvand; Pouran Raeissi; Hamid Ravaghi; Mohammadreza Maleki (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: The consequences induced by the natural disasters such as damage to food systems and destruction of livelihood-related infrastructure can threaten the food security of the people. Hence, food security measures are one of the most important responses concerning the management of natural disasters. This study was conducted to identify the challenges of food security response following natural disasters in Iran. MATERIALS AND METHODS: This study was conducted using a qualitative approach. The data were collected through semi-structured interviews with 29 key subjects; selected using purposive sampling. The qualitative content analysis was run to analyze the data collected. RESULTS: Based on the findings of this study, food security response challenges following the occurrence of natural disasters in Iran were classified into three main themes: (1) underlying challenges, (2) challenges of process and resources management, and (3) challenges of organizing and coordinating. These themes consisted of 11 subthemes. CONCLUSION: Following the occurrence of natural disasters, the management challenges, as well as the lack of coordination and organization between the stakeholders, are the serious challenges to achieving food security. Meanwhile, underlying challenges like climate change in the context of unsustainable living conditions of the vulnerable people have aggravated the food security response challenges.